Dynamic behavior of a fishing vessel in the Peruvian sea - Gamarra Chinchay, Hugo Eliseo (2011)
This paper describes the methodology used to predict the behavior presented by a displacement boat when it sails in certain sea conditions. It is important that the naval engineer determines this behavior in the design phase of the boat, because this way you can evaluate the adverse performance, such as the rise of the propellant, shipping water on deck, slamming and excessive accelerations vertical. The harmful effects described above are predicted by the response spectra of the vessel for a given sea condition and for a given movement. The procedure used for obtaining Response Spectra consists of overlapping Unitary Operator Response in regular waves for a given vessel movement (RAO) and the energy spectrum of Pierson-Moskowitz, used to represent the sea in a certain condition. The operator of the boat united response was determined using a Dynamic Vessel program based on the Theory of slices (Strip Theory) and, the various sea conditions considered, were characterized using meteorological data as significant height (Hs) and mean period (Tm) of the waves, these data being important in the generation of the energy spectrum for a given sea state. It also shows the results of the behavior of a fishing vessel operating in various conditions typical of the Peruvian coast. Adverse effects were determined and assessed for severity in the performance of the boat through design.